A Novel Mutation of the Calcium-Sensing Receptor Gene Causing Familial Hypocalciuric Hypercalcemia Complicates Medical Followup after Roux-en-Y Gastric Bypass: A Case Report and a Summary of Mutations Found in the Same Hospital Laboratory - Elin Rebecka Carlsson; Mai-Britt Toft Nielsen; Anne Mette Høgh; Rikke Veggerby Grønlund; Mogens Fenger; Louise Ambye (Case Reports in Endocrinology)
Heterozygous inactivating mutations in the calcium-sensing receptor (CaSR) gene are known to cause familial hypocalciuric hypercalcemia (FHH), usually a benign form of hypercalcemia without symptoms of a disrupted calcium homeostasis. FHH can be mistaken for the more common primary hyperparathyroidism (PHPT), for which surgical treatment may be needed. We describe a case of a 36-year-old woman with hypercalcemia and elevated PTH, initially suspected of having PHPT. Sequencing of the CaSR-gene revealed a mutation in nucleotide 437, changing the amino acid in position 146 from Glycine to Aspartate. The mutation was previously undescribed in the literature, but a very low calcium:creatinine clearance ratio supported the diagnosis FHH. A few years later, the patient’s two daughters were tested and the association between mutation and hypercalcemia could be confirmed. The patient was gastric bypass-operated and therefore, due to malabsorption and increased risk of fracture, was in need of adequate calcium supplementation. The chronically elevated calcium levels challenged medical followup, as calcium sufficiency could not be monitored in a traditional manner. Eventually the patient developed elevated alkaline phosphatase, a further increased PTH and a decreased DXA T-score indicating calcium deficiency and bone resorption. As a supplement, all CaSR-mutations found at our hospital, 2005-2018.